CRIMINAL LAW POLICY ON ECOCIDE AS A SERIOUS HUMAN RIGHTS VIOLATION IN INDONESIA - Herdi Hidayat; Muhyi Mohas; Reine Rofiana (Sriwijaya Crimen and Legal Studies, 2026)
This study is motivated by humanity’s arbitrary treatment of the environment, which has given rise to a new term: ecocide. Indonesian law has not yet recognized ecocide as a grave violation of human rights. This has resulted in weak enforcement of environmental laws against perpetrators and limited access to justice for victims. Unlike previous studies, which generally only discuss ecocide as an environmental crime that violates ordinary human rights, this study analyses ecocide through the perspective of gross human rights violations and determines the direction of criminal law policy needed to accommodate this concept within national law. The methods used in this study are normative legal research employing a statutory approach and a conceptual approach. The data were derived from secondary sources, including primary and secondary legal materials, as well as literature obtained through a literature review. The findings indicate that ecocide shares the same characteristics as gross human rights violations, namely the elements of widespread and systematic nature; this is what distinguishes it from ordinary environmental crimes. Indonesia’s environmental legal policy, through the Environmental Protection and Management Law (UU PPLH), already provides for criminal sanctions and fines; however, these regulations are not yet optimal. This is due to the lack of provisions categorizing ecocide as a form of gross human rights violation, making it difficult to prosecute perpetrators under a robust legal framework. This study proposes a formulation of criminal law policy through amendments to the Human Rights Court Law and the inclusion of ecocide as a gross human rights violation. Key points to consider include: recognizing corporations as legal entities that can be held accountable; optimizing the concept of strict liability; making criminal sanctions the primary remedy; and ensuring the fulfillment of victims’ rights through compensation, restitution, restoration of damaged environments, and socio-economic rehabilitation.